2004
DOI: 10.1177/004947550403400218
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile in Chronic Suppurative Otitis Media in Eastern Nepal

Abstract: Aural swabs were collected from 250 patients with chronic suppurative otitis media (CSOM) (tubotympanic disease). Duration of ear discharge was more than 6 months for culture and sensitivity test. The disease was unilateral in 178 (71.2%) and bilateral in 72 (28.8%) patients. From a total of 322 aural swab cultures, 324 organisms were isolated with predominance of Pseudomonas aerugimosa (36.4%) followed by Staphylococcus aureus (30.2%). All the isolated Gram-negative organisms showed in vitro sensitivity to ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 3 publications
5
25
0
1
Order By: Relevance
“…Similar bacterial isolates were noted by Choi et al [8]. P. aeruginosa and S. aureus were the frequent isolates observed by studies from our country as well as our neighboring countries too [3,7,[9][10][11][12]. Park et al [13] too have noted methicillin-resistant S. aureus (24.8%) in their isolates.…”
Section: Discussionsupporting
confidence: 88%
“…Similar bacterial isolates were noted by Choi et al [8]. P. aeruginosa and S. aureus were the frequent isolates observed by studies from our country as well as our neighboring countries too [3,7,[9][10][11][12]. Park et al [13] too have noted methicillin-resistant S. aureus (24.8%) in their isolates.…”
Section: Discussionsupporting
confidence: 88%
“…19 Sharma et al reported Pseudomonas in 36% cases. 20 In our study, Staphylococcus aureus and Pseudomonas sp. together account for about 67.24 % of cases, which is in accordance with the study by Aslam et al…”
Section: Discussionmentioning
confidence: 57%
“…This is comparable with other studies done elsewhere. 11,21,30,31,32 The in-vitro efficacy of gentamicin, ceftriaxone and ciprofloxacin against tested organisms in present study is the reflection of infrequent prescription of these drugs by ENT specialist in the community.…”
Section: Resultsmentioning
confidence: 72%
“…aeruginosa, Proteus and E. coli. 11 Microbial drug resistance is a growing global problem bacteria like E. coli, Klebsiella spp. and P. aeruginosa and increasing trends are observed for all major anti-Gram negative agents (beta-lactams, fluoroquinolones and aminoglycosides).…”
mentioning
confidence: 99%